Anti-Candida Properties of Urauchimycins from Actinobacteria Associated with Trachymyrmex Ants. (18th March 2013) - Mendes, Thais D.; Borges, Warley S.; Rodrigues, Andre; Solomon, Scott E.; Vieira, Paulo C.; Duarte, Marta C. T.; Pagnocca, Fernando C.
Abstract : After decades of intensive searching for antimicrobial compounds derived from actinobacteria, the frequency of isolation of new molecules has decreased. To cope with this concern, studies have focused on the exploitation of actinobacteria from unexplored environments and actinobacteria symbionts of plants and animals. In this study, twenty-four actinobacteria strains isolated from workers of Trachymyrmex ants were evaluated for antifungal activity towards a variety of Candida species. Results revealed that seven strains inhibited the tested Candida species. Streptomyces sp. TD025 presented potent and broad spectrum of inhibition of Candida and was selected for the isolation of bioactive molecules. From liquid shake culture of this bacterium, we isolated the rare antimycin urauchimycins A and B. For the first time, these molecules were evaluated for antifungal activity against medically important Candida species. Both antimycins showed antifungal activity, especially urauchimycin B. This compound inhibited the growth of all Candida species tested, with minimum inhibitory concentration values equivalent to the antifungal nystatin. Our results concur with the predictions that the attine ant-microbe symbiosis may be a source of bioactive metabolites for biotechnology and medical applications.